Hechtius (1795-1798) - the beginnings of historical-philosophical-idiographic research in comparative education - Lenhart, Volker (Comparative education, 2018)
From its very beginnings, we can discern two methodological approaches to comparative education; one broadly historical-philosophical-idiographic and another broadly empirical-positivist-nomothetic. Friedrich August Hecht's 1795-1798 De re scholastica Anglica cum Germanica comparata (English and German school education compared), with its hermeneutic textbook analysis, represents an idiographic methodology. Whilst the 1816/1817 data-driven research programme of Marc-Antoine Jullien - usually considered the origin of comparative education - represents an empirical-positivist-nomothetic approach. In this essay, we will examine the theoretical orientations of Hecht's study - his ideas of transnationality and national character, and his avoidance of the proposal of borrowing and lending. We situate the beginnings of Hecht's methodology in its social-historical context and analyse the transfer of interpretation methods from philology to comparative education. Finally, we will postulate a combination of Jullien's and Hecht's methodological approaches.
Published online: 13 Nov 2017
Gesehen am 27.02.2020